(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
Summary: 1. Introduction - 2. Italian legal responses to COVID-19: the Italian constitutional and legal framework on religious freedom - 3. The suspension of religious assemblies during phase one of the pandemic - 4. A “cautious resumption” of religious gatherings during the phase two in Italy - 5. U.S. legal responses to COVID-19: U.S. constitutional and legal framework about religious freedom - 6. The legal patchwork because of the pandemic - 7. Judicial balance between individual liberties and the preservation of health - 8. Litigation in lower courts about the exercise of religious freedom during Covid-19 - 9 New creative ways of worshipping in Covid-19 times: drive-in religious services - 10. Third-party burdens and the successful nondiscrimination approach - 11. Department of Justice statements - 12 Supreme Court intervention in temporary state restrictions on religious assemblies - 13. “Religious America” and “secular” Italy during Covid-19 phase one - 14. Management of religious freedom during the pandemic and the lack or presence of a statute governing religious freedom - 15. Effect of the pandemic on the question of whose religious freedom should be protected - 16. Guaranteeing a fair level of religious accommodation during a pandemic - 17. Enhanced need to balance the exercise of religious freedom with third-party harm during a pandemic - 18. Impact of the pandemic on the exercise of religious freedom in the long term. ABSTRACT: The so-called lockdown, imposed to restrain (or at least limit) the spread of COVID-19, has, in the over four seemingly endless months since it started, had an overwhelming impact not only on our personal lives, but also on domestic regulatory frameworks. Legal systems responded individually, and with differences to the pandemic emergency, ranging from a complete interruption of the collective exercise of religious worship (Italy), to a more cautious recognition of forms of religious accommodation (United States). The present paper compares the impact of COVID-19 restrictions on the exercise of religious freedom in the United States and the Italian legal contexts, and investigates how the pandemic crisis emphasized underlying judicial, political, sociocultural, and economic challenges, giving rise to a tension between competing rights and exacerbating concerns about the “special” role of religion. As the COVID situation is changing so rapidly in the United States, in Italy, and around the world, I clarify that the information in the present paper relates at the situation as at the end of June 2020.